FEAR OF DEATH IS AN EXISTENTIAL DRAMA OF HUMAN EXISTANCE - Ільящук, Альона (SWorldJournal, 2024)
The article analyzes the fear of death and its impact on life in the context of psychology and philosophy. Different approaches to the problem and the role of the fear of death in the formation of values are considered. Defense strategies are also describ